The Women Representation in Detergent Product Packaging Designs - Dinda Aryani (Passage, 2013)
Gender representation in media often depicts gender stereotype. For example, women representation in a particular culture and society shows what women should do and how to behave. Regarding this, the present study titled “The Women Representation in Detergent Product Packaging Designs” aims to reveal how women are represented in detergent product package and what ideology is conveyed behind these representations. Employing descriptive qualitative method to analyze visual images and reveal women representation, this study is framed under the Social Semiotics theory of Reading Images proposed by Kress and van Leeuwen (2006). On the other hand, the ideology is disclosed by using Barthes’ Signification Order. The results show that women are mostly represented as feminine, gentle, motherly, mature, independent, warm, caring, loving, attractive, friendly and happy. In consequence, the ideology relayed is ideology of feminity. This ideology is conveyed through several ways including media codes such us fashion, colors, and non-verbal codes. Key Words: Visual images, Women Representation, Ideology of Feminity, Social Semiotics, Reading Images